2021
DOI: 10.1101/2021.05.31.446412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D atlas of the pituitary gland of the model fish medaka

Abstract: In vertebrates, the anterior pituitary plays a crucial role in regulating several essential physiological processes via the secretion of at least seven peptide hormones by different endocrine cell types. Comparative and comprehensive knowledge of the spatial distribution of those endocrine cell types is required to better understand their role during the animal life. Using medaka as the model and several combinations of multi-color fluorescence in situ hybridization, we present the first 3D atlas revealing the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…We further investigated the identity of the pituitary cells expressing these receptors. The RPD of teleosts, including medaka, contains prolactin (prl)-and pro-opiomelanocortin (pomc)-expressing cells, whereas the PI contains somatolactin (sl)-and pomcexpressing cells 28 . Double in situ hybridization for the receptors and pituitary hormone genes showed that adcyap1r1a was expressed in pomc-, but not prl-expressing, cells in the RPD and adcyap1r1b and vipr2b were exclusively expressed in sl-and pomc-expressing cells, respectively, in the PI (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We further investigated the identity of the pituitary cells expressing these receptors. The RPD of teleosts, including medaka, contains prolactin (prl)-and pro-opiomelanocortin (pomc)-expressing cells, whereas the PI contains somatolactin (sl)-and pomcexpressing cells 28 . Double in situ hybridization for the receptors and pituitary hormone genes showed that adcyap1r1a was expressed in pomc-, but not prl-expressing, cells in the RPD and adcyap1r1b and vipr2b were exclusively expressed in sl-and pomc-expressing cells, respectively, in the PI (Fig.…”
Section: Resultsmentioning
confidence: 99%